Acidification during aerobic treatment of digested swine wastewater and its effect on pollutant removal. Issue 5 (28th May 2017) - Wang, Shen; Deng, Liangwei; Xu, Ze; Zheng, Dan; Wang, Lan
ABSTRACT: Digested swine wastewater effluent was treated in sequencing batch reactors at different hydraulic retention times (HRTs), and the acidification process and its effects on pollutant removal were investigated. At influent chemical oxygen demand (COD) and concentrations of 540 mg/L and 400 mg/L, respectively, all reactors experienced acidification due to nitrification, and the lowest pH values reached approximately 6. The COD removals were −22.1%, −14.3% and 3.23%, and removals were 70.1%, 77.0% and 80.7% in reactors with HRTs of 1.25, 2.5, and 5 days, respectively. Practically, no TP was removed. At HRTs of 7.5, 10 and 12.5 days, COD removal reached 4.34%, 5.46% and 8.88%, respectively, and removal reached 81.1%, 82.3% and 83.0%, respectively. Although longer HRT increased the removal of, it decreased the removal rate. Acidification significantly restricted the performance of reactors. Low pH not only inhibited the growth and metabolism of microorganisms, but also influenced the availability and toxicity of substrates and products of nitrifying bacteria. Acidification was also responsible for leakage of phosphate from microbial cells and the dissolution of precipitated phosphorus.